Theoretical Performance Study of a Novel Diffusion Absorption Heat Transformer Driven by a Jet Pump - Shikuan Wang; Zhaojie Wu; Shaoqiu Jiang; Yuncheng Li; Hongtao Gao (Energies)
A diffusion absorption heat transformer is a completely thermally driven heat upgrading technology with significant application potential in low-grade thermal energy recovery. However, existing diffusion absorption heat transformers have problems such as complex circulation processes, limited solution flow rates, and insufficient stability due to their reliance on bubble pumps. A jet pump was proposed for application in a diffusion absorption heat transformer cycle to replace the bubble pumps in the original diffusion absorption heat transformer cycle. In the novel cycle, without electricity consumption, the diffusant gas was used as the primary flow of the jet pump to transport the solution, and the diffusion generation of the refrigerant was realized in the jet pump for more efficient and stable thermal energy upgrading. The performance of the novel cycle with H2O/LiBr/C5H10 or H2O/HCOOK/C5H10 as working fluids was analyzed based on a constructed theoretical model validated by numerical simulation. It was found that the performance of the jet pump was sensitive to the generator temperature and the pressure difference of the cycle. Increasing the temperature of the jet pump and reducing the temperature of the absorber were conducive to improving the COP. As a potential absorbent substitute for LiBr, HCOOK also led to slightly better performance in most cases.